2020
DOI: 10.3390/jpm10030135
|View full text |Cite
|
Sign up to set email alerts
|

Is Structured Exercise Performed with Supplemental Oxygen a Promising Method of Personalized Medicine in the Therapy of Chronic Diseases?

Abstract: Aim: This systematic review aimed to explore the literature to identify in which types of chronic diseases exercise with supplemental oxygen has previously been utilized and whether this type of personalized therapy leads to superior effects in physical fitness and well-being. Methods: Databases (PubMed/MEDLINE, CINHAL, EMBASE, Web of knowledge and Cochrane Library) were searched in accordance with PRISMA. Eligibility criteria included adult patients diagnosed with any type of chronic diseases engaging in supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 109 publications
(338 reference statements)
0
7
0
Order By: Relevance
“…Thus, supplemental oxygen could reduce ventilatory limitation during exercise and permit higher training loads/volume, also because of greater peripheral muscle activation and less fatigability (13), consequently leading to improved exercise capacity due to better training stimuli (28,30,33). Until publication of the results of our SCOPE study supporting the use of supplemental oxygen during training in nonhypoxemic COPD, the outcomes from previous studies were rather heterogenous (15–17). Different study designs and technical aspects of oxygen delivery might have contributed to the inconclusive discussion (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, supplemental oxygen could reduce ventilatory limitation during exercise and permit higher training loads/volume, also because of greater peripheral muscle activation and less fatigability (13), consequently leading to improved exercise capacity due to better training stimuli (28,30,33). Until publication of the results of our SCOPE study supporting the use of supplemental oxygen during training in nonhypoxemic COPD, the outcomes from previous studies were rather heterogenous (15–17). Different study designs and technical aspects of oxygen delivery might have contributed to the inconclusive discussion (16).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unresolved whether nonhypoxemic COPD patients should exercise with supplemental oxygen (5,(15)(16)(17). Several studies have applied oxygen during endurance exercise training in patients with (18)(19)(20)(21)(22)(23)(24)(25) and without exertional hypoxemia (26)(27)(28)(29), with conflicting results in both cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…He emphasized the importance of using air mixture enriched with oxygen in patients with numerous chronic diseases, such as obesity, during physical training. 19…”
Section: Oxygen As An Important Element In the Treatment Of Obesitymentioning
confidence: 99%
“…What remains unsolved, however, is whether non‐hypoxemic COPD patients should exercise with supplemental oxygen 9,11 . Several studies have applied oxygen during exercise training in patients with COPD, showing conflicting results 12‐25 . However, we have previously shown that supplemental oxygen might improve the training effect on peak exercise capacity, when high oxygen flow rate, oxygen‐specific exercise prescription and progressive adaptation of high‐intensity interval training is provided 20,26,27 …”
Section: Introductionmentioning
confidence: 99%